ANALYSIS OF CONTEXTUAL MEANINGS IN SABRINA CARPENTER'S SONG LYRICS 'NONSENSE': A SEMANTIC STUDY - Dwi Permata Sari; Rawuh Yuda Yuwana (PT Akselerasi Karya Mandiri, 2024)
This study analyzes the contextual meaning in the lyrics of the song “Nonsense” by Sabrina Carpenter. The findings reveal that the lyrics convey meanings both directly and indirectly, with several expressions relying heavily on context for accurate interpretation. Through semantic analysis, the study demonstrates how figurative language, playful innuendos, and situational references in the song reflect the songwriter’s intent and emotional nuance. The results highlight the significance of context in interpreting song lyrics and contribute to a deeper understanding of how meaning is constructed in contemporary pop music.